Estimation of adsorption parameters from temperature-programmed-desorption thermograms application to the adsorption of carbon dioxide onto Na- and H-mordenite - Delgado, José A (Langmuir : the ACS journal of surfaces and colloids, 2005)
In this work, a model is proposed for the estimation of the adsorption parameters from TPD thermograms when the adsorption cell can be modeled as a well-mixed reactor, evaluating the adsorption and desorption rate constants from statistical thermodynamics. The estimation procedure consists of fitting the model to the experimental TPD thermograms using numerical methods. The study of the effect of readsorption in this system reveals that this effect must be taken into account in most cases. Only with high activation energies of adsorption may this effect be negligible. The model is used to estimate the adsorption parameters of the systems CO(2)-Na-mordenite and CO(2)-H-mordenite, including an analysis about the degrees of freedom of the adsorbed phase. The estimated values of the adsorption enthalpy have been compared with the ones obtained from adsorption equilibrium data